ASSESSMENT OF THE RELATIONSHIP BETWEEN THE MAIN ECONOMICALLY VALUES OF THE VARIETY OF LETTUCES - O. N. Bobkova; V. V. Skorina (Овощи России, 2019)
Expanding the range of vegetable crops, including green ones, through the introduction of new varieties into production is an important task. The study and evaluation of the original material of the salad, the features of cultivation in different periods, will allow to identify samples of a complex of economically valuable traits for the selection of culture, which is relevant for the creation of varieties in Belarus. Research was carried out on the experimental field of the Department of horticulture of the Belarusian state agricultural Academy in 2013-2015. The article assesses the relationship between the main economically valuable features of varieties of lettuce when grown in the spring (seedling method) and spring and summer sowing in the open ground. In lettuce plants of the headed variety, the sign “the mass of the vegetative part of the plant” strongly depends on the sign “diameter of the head” (r=0.640 - with the seedling method and r=0.809 - with the spring sowing period), “leaf width” (r=0.685 and r=0.790, respectively). A high connection is also established between the signs "leaf length" and "leaf width" (r=0.702 - with the spring sowing period and r=0.749 - with the seedling method). In leaf lettuce plants, a strong correlation was noted between the signs “leaf length” and “plant height” (r=0.706 for summer and r=0.810 for spring planting), diameter of the rosette of leaves (r=0.564 for summer and r=0.810 - at the spring sowing time). The average feedback for leaf lettuce varieties is revealed between the signs “leaf width” and “number of leaves” (r=-0.444 - for spring and r=-0.458 - for summer sowing time). The majority of morphological signs, depending on the time of cultivation, are related to each other by average correlation links (the correlation coefficient ranged from 0.458 to 0.531).